One‐Pot Synthesis of 2‐(Aryl/Alkyl)amino‐3‐cyanobenzo[b]thiophenes and Their Hetero‐Fused Analogues by Pd‐Catalyzed Intramolecular Oxidative C–H Functionalization/Arylthiolation. Issue 37 (9th October 2017) - Saraiah, Bonagiri; Gautam, Vibha; Acharya, Anand; Pasha, Mohamed A.; Hiriyakkanavar, Ila
Abstract : We have developed a high‐yielding synthesis for substituted 2‐(aryl/alkyl)amino‐3‐cyanobenzo[ b ]thiophenes and their hetero‐fused analogues by using a palladium‐catalyzed intramolecular oxidative C–H functionalization/arylthiolation reaction of in situ generated N ‐(alkyl/aryl)thioamides, prepared from readily available (hetero)arylacetonitriles and alkyl/aryl isothiocyanates. This protocol was then extended to the synthesis of amino‐substituted benzothieno[2, 3‐ b ]quinolines by employing a triflic acid mediated intramolecular cyclocondensation of the prepared 2‐arylamino‐3‐cyanobenzo[ b ]thiophenes. Abstract : An efficient one‐pot synthesis has been developed for substituted 2‐(aryl/alkyl)amino‐3‐cyanobenzo[ b ]thiophenes and their hetero‐fused analogues by using (hetero)arylacetonitriles and aryl/alkyl isothiocyanates in a Pd II ‐catalyzed C–H functionalization/arylthiolation reaction. Some of the 2‐arylamino‐3‐cyanobenzo[ b ]thiophenes were successfully converted into benzothieno[2, 3‐ b ]quinolones. DMSO = dimethyl sulfoxide; Tf = trifluoromethanesulfonyl; DCE = 1, 2‐dichloroethane.